2008
DOI: 10.12702/1984-7033.v08n04a10
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and amplification of simple sequence repeat loci in coffee

Abstract: -Simple sequence repeat (microsatellite) loci in coffee were identified in clones isolated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Moreover, the group maintains a strong collaboration with the Sol Genomics Network (SGN) as the mirror of their site in Colombia. Besides building a very robust platform for research on coffee, Cenicafé has performed such important advances as coffee genomics [3]–[5], coffee genetic diversity studies [6], the understanding of plant resistance to diseases and pests [7], the molecular study of coffee pathogens [8][10], and the diversity of Beauveria bassiana [11], a fungus with biological control potential not only for coffee pests, but for a wide spectrum of other plant diseases in Colombia.…”
Section: Researchmentioning
confidence: 99%
“…Moreover, the group maintains a strong collaboration with the Sol Genomics Network (SGN) as the mirror of their site in Colombia. Besides building a very robust platform for research on coffee, Cenicafé has performed such important advances as coffee genomics [3]–[5], coffee genetic diversity studies [6], the understanding of plant resistance to diseases and pests [7], the molecular study of coffee pathogens [8][10], and the diversity of Beauveria bassiana [11], a fungus with biological control potential not only for coffee pests, but for a wide spectrum of other plant diseases in Colombia.…”
Section: Researchmentioning
confidence: 99%
“…Low polymorphism was also reported by Combes et al (2000), who only identified five polymorphic microsatellite markers among 11 SSR primers tested in C. arabica. Furthermore, Cristancho and Gaitan (2008) also identified five polymorphic markers among 12 SSR markers tested in tetraploid Coffea.…”
Section: Discussionmentioning
confidence: 93%
“…Low polymorphism of molecular markers among progenies of C. arabica is well documented (Lashermes et al, 1999;Bertrand et al, 2001), since this species has a narrow genetic base, is autogamous in nature, tetraploid (Cristancho and Gaitan, 2008), and has a low frequency of microsatellite regions in the genome (Cristancho and Gaitan, 2008;AlMurish et al, 2013). Furthermore, in this case, all progenies originated from the crossing of two genotypes.…”
Section: Discussionmentioning
confidence: 98%
“…TEs frequently have multiple transposase binding sites adjacent to their TIRs [ 33 , 39 - 42 ]. In other hAT elements, such as Ac, Tol2 and Tag1 , their respective transposases bind to short sequence repeats [ 31 , 33 , 34 , 43 ].…”
Section: Discussionmentioning
confidence: 99%